2003
DOI: 10.1002/jnr.10655
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and cell type‐specific expression of the neuronal marker NeuN in the murine cerebellum

Abstract: NeuN is a 46/48-kD nuclear protein antigen used widely to identify postmitotic neurons in both research and diagnostics. It is expressed by neurons throughout the nervous system of a variety of species, including birds, rodents, and man (Mullen et al. [1992] Development 116:201-211). When we sought to use NeuN to follow the developmental progression of murine cerebellar interneurons, we observed that expression of this antigen in the cerebellum was restricted to granule neurons and a small population of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
195
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(213 citation statements)
references
References 41 publications
(53 reference statements)
15
195
0
1
Order By: Relevance
“…COX2-positive labelling co-localized with immunoreactivity for NeuN (figure 1a-e), a 46/48 kD neuronal nuclear protein antigen widely used to identify neurons [65,66].…”
Section: Results (A) Behavioural Observations and Effect Of 7nimentioning
confidence: 99%
“…COX2-positive labelling co-localized with immunoreactivity for NeuN (figure 1a-e), a 46/48 kD neuronal nuclear protein antigen widely used to identify neurons [65,66].…”
Section: Results (A) Behavioural Observations and Effect Of 7nimentioning
confidence: 99%
“…Their phenotypes were determined on the basis of several criteria, including (1) morphological features, (2) expression of type-specific markers, (3) morphometric parameters (e.g., cell body size), and (4) position in the host cortical layers or deep nuclei. The different types of GABAergic interneurons were identified according to the expression pattern of a set of distinctive markers and assigned to different categories: deep nuclei interneurons [NeuN/calretinin (Bastianelli, 2003;Weyer and Schilling, 2003)]; granular layer interneurons for Golgi [mGluR2/Pax-2 Grimaldi and Rossi, 2006)] and Lugaro cells [calretinin (Dino et al, 1999;Bastianelli, 2003)]; and molecular layer interneurons for basket and stellate cells [parvalbumin (Celio, 1990)]. Except for rare elements ectopically positioned in the white matter (see below and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Among the markers applied to distinguish between these types in adult rats, we found that NeuN labels the nucleus and perikaryal cytoplasm of virtually all nuclear neurons (Figs. 2 A, 3C,D) (Mullen et al, 1992;Weyer and Schilling, 2003). In contrast, SMI32 and calretinin identify two primarily nonoverlapping neuronal subsets (of a sample of 1310 neurons, only 27 were double labeled): the former marker decorates large polygonal neurons (Figs.…”
Section: Birthdates Of Deep Nuclei Neuronsmentioning
confidence: 99%
“…6 B, G), which marks the fraction of differentiating granule cells on their way from the external cell layer into deeper layers of the cerebellum (Weyer and Schilling, 2003). This was similarly observed in transgenic and wild-type cerebella.…”
Section: Transgenic Cerebella Contain the Major Types Of Cerebellar Nmentioning
confidence: 59%
“…This was similarly observed in transgenic and wild-type cerebella. Differentiating and differentiated granule cells in deeper layers of wild-type cerebella express high levels of NeuN (Weyer and Schilling, 2003). NeuN immunoreactivity in deeper regions was also observed in transgenic cerebella, arguing that granule cells differentiate in this genotype despite the obvious absence of an orderly internal granule cell layer (Fig.…”
Section: Transgenic Cerebella Contain the Major Types Of Cerebellar Nmentioning
confidence: 74%